On highly efficient derivative-free family of numerical methods for solving polynomial equation simultaneously - Shams, Mudassir; Rafiq, Naila; Kausar, Nasreen; Agarwal, Praveen; Park, Choonkil; Mir, Nazir Ahmad (SPRINGER, 2021)
A highly efficient new three-step derivative-free family of numerical iterative schemes for estimating all roots of polynomial equations is presented. Convergence analysis proved that the proposed simultaneous iterative method possesses 12th-order convergence locally. Numerical examples and computational cost are given to demonstrate the capability of the method presented.
Keywords: Numerical scheme; Polynomials; Computational efficiency; CPU-time; Convergence order; ROOT-FINDING METHODS; ITERATIVE METHODS; SIMULTANEOUS APPROXIMATION; NONLINEAR EQUATIONS; CONVERGENCE; ZEROS; DISTINCT; Mathematics